Self Care Behavior As An Indicator Of Psychological Adaptation In Patients Undergoing Chemotherapy - Awatiful Azza (Journal of Global Pharma Technology, 2020)
Background: Chemotherapy is one of the medical actions taken to treat cancer and kill cancer cells using cytostatic drugs. This treatment not only has positive effects but also the negative effects of sufferers. This study aims to analyze the relationship of self-care behavior with the psychological adaptability of patients undergoing chemotherapy Methode: This study used a cross-sectional design. The Sample was 120 patients in the chemotherapy treatment unit at the hospital in Jember-Indonesia district, with purposive sampling. The independent variables were self-care behavior (include self-care confidence, self-care management, Self-care maintenance). The dependent variable was a psychological adaptation. Data were obtained through a modified Self Care Heart Failure In-dex (SCHFI) instrument which has been modified for patients undergoing chemotherapy. Data were analyzed by using Chi-square with a significance level of p < 0, 05. Results: of this study indicate there was a relationship between self-care behavior with the psychological adaptability of patients with chemotherapy, the p-value was 0.00 <0.05. Conclusion: Self-care behavior is one form of nursing service that can be applied to patients undergoing chemotherapy. The ability to engage patients independently during chemotherapy can increase patient self-esteem and will help improve patient adaptation due to the side effects of chemotherapy. Further study recommends developing the intervention to improve the adaptation of patients undergoing chemotherapy.Keywords: Adaptation, Self Care Behavior, Chemotherapy.